SISTEM BAGI HASIL PADA PERUSAHAAN TRAVEL DI KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH TINJAUAN KOMPILASI HUKUM EKONOMI SYARIAH - Bella Deva Meilandri; Rasiam Rasiam; Suhardiman Suhardiman (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
The purpose of this study was to determine the practice of profit sharing at the Faqih Family Travel Company through the study of the Sharia Economic Law Compilation (KHES). Researchers used qualitative methods with field research and juridical-empirical approaches. Sourced from primary data in the form of observations, interviews, and primary book materials, namely (KHES). In contrast, secondary data are articles, journals, and websites on the internet. Data collection techniques are observation, interviews, and documentation. From the collected data, researchers check the validity through a series of time triangulation and member-check. Then, it is analyzed through data reduction, data presentation, verification, and concluding. The results showed that the practice of profit sharing at the Faqih Family Travel Company in Sungai Kunyit District, Mempawah Regency, was carried out at the end of each month depending on the number of consumers who used the services of the Faqih Family Travel Company based on the agreement agreed upon by all parties. There are two types of contracts in this profit-sharing practice: the first syirkah 'inan is a contract between the company owner and the fleet owner because they both issue capital even though the amount is not the same. Based on the ijarah contract, a discrepancy with KHES occurred because it is unlike the first agreement with the drivers. Therefore, researchers recommend revising the agreement with parties to find a solution regarding the distribution of results which is not follow the first agreement. Keywords: Profit Sharing, Ijarah, Syirkah Al-'Inan